Description of three Rhacophorus tadpoles (Lissamphibia: Anura: Rhacophoridae) from Sarawak, Malaysia (Borneo) - Haas, A.; Hertwig, Stefan T.; Krings, Wenke; Braskamp, Enzo; Dehling, J. Maximilian; Pui, Yong Min; Jankowski, Andre; Schweizer, Manuel; Das, I. (Magnolia Press, 2012)
This communication reports the discovery of the hitherto unknown larval forms of Rhacophorus rufipes and R. penanorum, and re-describes the tadpole of R. dulitensis. Tadpoles of all three species were discovered at Gunung Mulu National Park, Sarawak (Borneo), Malaysia. The identity of the larvae was determined by DNA barcoding techniques using partial 16S rRNA mitochondrial gene sequences. Larval DNA sequences matched those of syntopic adults of respective species. Detailed descriptions of external morphology and colouration in life are provided along with ecological notes. The tadpole of R. rufipes and R. dulitensis can be classified as generalized, benthic-nectonic type, whereas tadpoles of R. penanorum show adaptations typical for a lotic, rheophilous lifestyle.